Tahafut At-Tahafut: Sanggahan Terhadap Tahafut Al-Falasifah - Aminah, Lailatul; Hanafi, Yusuf (UIN Sumatera Utara, 2025)
This article is a review of the book Tahafut At-Tahafut, written by Ibn Rusyd. The main focus of the discussion is Ibn Rusyd's criticism of Al-Ghazali's view of the concept of Eternity of the Universe (Qidam al-‘Alam), which highlights differences in understanding the origins, eternity, and relationship between time and motion in the context of the creation of the universe. The ideas and findings in this book are very useful for understanding Ibn Rushd's thinking more deeply in the context of classical Islamic philosophy. Ibn Rushd's criticism serves as a means to foster critical thinking among Muslims, so that they do not easily fall into blind imitation. The results of the study show that Tahafut al-Tahafut is Ibn Rushd's rational defense of philosophy and his attempt to harmonize reason with revelation. He emphasized that nature depends on the eternal will of God and made a significant contribution to the development of Islamic rationalism and Western thought. Despite its shortcomings in terms of linguistic complexity and heavy arguments, this work remains valuable as an important foundation for dialogue between Islamic philosophy and theology.